Cystoseira baccata meadows along the French Basque coast (Bay of Biscay) as a reference for the implementation of the Water Framework and Marine Strategy EU directives. (1st July 2019) - Casamajor, Marie-Noëlle de; Lalanne, Yann; Derrien-Courtel, Sandrine; Maria Gorostiaga, José; Le Gal, Aodren; Huguenin, Laura; Quintano, Endika; Lissardy, Muriel
Abstract: Cystoseira baccata, a biological quality element for the implementation of the Water Framework and Marine Strategy EU Directives, is a dominant species in the subtidal rocky bottoms of the Basque coast. As part of this issue and given the need to better understand the functional character of benthic rocky ecosystems and use them as a reference to anthropogenic changes, two samplings campaigns were conducted in 2014 and 2017. Several population parameters (i.e. frond density, frond length frond-length/total frond-length ratio and taxonomic richness of epibionts) of C. baccata were studied from three sites monitored within the Water Directive Framework in relation to bathymetry during the two campaigns. The results showed a significant influence of bathymetry on frond density, frond length and the epibiotic load, and also an effect of sampling time for the seaweed and epibionts (epiflora and epifauna). The characterization of these functional population parameters for C. baccata under natural conditions are extremely valuable for its application to monitoring programs evaluating the ecological status of coastal waters in this region. Highlights: Contribution of new knowledge on C. baccata habitat and population. Confirmation of interest of this engineering species in implementation MSFD. Swell effect influencing density and individual height. Ratio of length is pertinent metric to discriminate epibiosis considering levels.